Team leadership assessment after advanced life support courses comparing real teams vs. simulated teams - Nabecker, Sabine; Huwendiek, Sören; Roten, Fredy-Michel; Theiler, Lorenz; Greif, Robert (Frontiers in Psychology, 2022)
Aim of the study: Effective team leadership is essential during cardiopulmonary resuscitation and is taught during international advanced life support courses. This study compared the judgement of team leadership during summative assessments after those courses using different validated assessment tools while comparing two different summative assessment methods. Methods: After advanced life support courses, twenty videos of simulated-team assessments and 20 videos of real-team assessments were evaluated and compared. Simulated-team assessment used an instructor miming a whole team, whereas real-team assessment used course participants as a team that acted on team leader’s commands. Three examiners individually evaluated each video on four different validated team leadership assessment tools, and on the original European Resuscitation Councils’ scenario-test assessment form which does not assess leadership. The primary outcome was the averaged performance summary score between all three examiners for each assessment method. Results: The averaged performance summary score for each of the four assessment tools was significantly higher for real team assessments compared to simulated team assessments (all p<0.01). The summary score of the European Resuscitation Councils’ scenario-test assessment form was comparable between both assessment methods (p=0.569), meaning that participants of both assessments performed equally. Conclusion: Team leadership performance is rated significantly higher in real-team summative assessments after advanced life support courses compared to simulated-team assessments by four leadership assessment tools but not by the standard European Resuscitation Council’s scenario-test assessment form. These results suggest that summative assessments in advanced life support courses should integrate real-team assessments and a new assessment tool including an assessment of leadership skills needs to be developed. Key words: education, assessment, CPR, advanced life support, ERC, human factors